Analysis of Factors Affecting Work Productivity - Atoillah, Atoillah; Rustandi, Tata; Permana, Angrian (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
One of the responsibilities of heavy manufacturing and construction companies is high work risk and high productivity demands. These conditions require the implementation of good work discipline, safety, and occupational health to support employee performance. This study aims to analyze the effect of work discipline, safety, and occupational health on job satisfaction and its implications for productivity in a manufacturing company in Indonesia. This study uses a quantitative method with regression analysis tools, through the distribution of questionnaires to 98 respondents using purposive sampling techniques in the design, manufacturing, and steel structure construction divisions. The data was analyzed using the SmartPLS statistical application. The results show that work discipline, safety, and occupational health have a positive effect on job satisfaction, and both have a direct effect on productivity. Job satisfaction was also proven to be a factor that contributes to increased productivity. The implications of this study are improvements in work discipline and job satisfaction as well as employee productivity. Optimal occupational safety and health management contributes to the creation of sustainable job satisfaction. A safe and healthy work environment encourages employees to achieve their best performance.